2017
DOI: 10.1371/journal.pone.0170188
|View full text |Cite
|
Sign up to set email alerts
|

Migratory timing, rate, routes and wintering areas of White-crested Elaenia (Elaenia albiceps chilensis), a key seed disperser for Patagonian forest regeneration

Abstract: Migratory animals often play key ecological roles within the communities they visit throughout their annual journeys. As a consequence of the links between biomes mediated by migrants, changes in one biome could affect remote areas in unpredictable ways. Migratory routes and timing of most Neotropical austral migrants, which breed at south temperate latitudes of South America and overwinter closer to or within tropical latitudes of South America, have yet to be described in detail. As a result, our understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 51 publications
1
50
0
2
Order By: Relevance
“…However, Fork‐tailed Flycatchers from across different sites migrated at a similar pace. Notably, the spring migration rates exhibited by austral migrant Fork‐tailed Flycatchers (i.e., ~134 km/day) are similar to those of another austral migrant flycatcher, the White‐crested Elaenia, which migrates on average between 121 and 261 km/day (Bravo et al, ).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, Fork‐tailed Flycatchers from across different sites migrated at a similar pace. Notably, the spring migration rates exhibited by austral migrant Fork‐tailed Flycatchers (i.e., ~134 km/day) are similar to those of another austral migrant flycatcher, the White‐crested Elaenia, which migrates on average between 121 and 261 km/day (Bravo et al, ).…”
Section: Discussionmentioning
confidence: 75%
“…Bird migration across the New World is ubiquitous, from high Arctic tundra to Patagonia, and research on the mechanisms underpinning avian migratory patterns in the New World and beyond continues to be a rapidly growing area of inquiry. Such studies have shown that the timing and pace of migration and the location of migratory routes can vary widely not only between species, but also between populations within a species (e.g., Sylvia warblers, Fransson, ; Collared flycatchers, Ficedula albicollis , Briedis et al, ; Northern wheatears, Oenanthe oenanthe , Bairlein et al, ; Wood thrushes, Hylocichla mustelina , Stanley, MacPherson, Fraser, McKinnon, & Stutchbury, ; White‐crested elaenias, Elaenia albiceps , Bravo, Cueto, & Gorosito, ). Understanding the causes of such variation is vital for developing a basic understanding of the evolution and regulation of migration, as well as for evaluating the fitness consequences of employing a given migratory strategy, since processes that occur in one season can influence the survival and reproduction of an individual in subsequent seasons (i.e., through carryover effects, reviewed by Harrison, Blount, Inger, Norris, & Bearhop, ).…”
Section: Introductionmentioning
confidence: 99%
“…Th e White-crested Elaenia (Elaenia albiceps chilensis) is the most abundant Neotropical austral migrant passerine at the Patagonian forest (Grigera et al 1994, Ippi et al 2009. Th is tyrant fl ycatcher arrives up to mid-October to breed and start its migration to the tropics between mid-February and March (Fitzpatrick 2004, Bravo et al 2017. It is a frugivorous-insectivorous species with an important role as the main disperser of seed of endemic plants of the Patagonian forest (Armesto et al 1987, Amico & Aizen 2005 and as a controller of herbivorous insects of Nothofagus trees (Mazia et al 2009).…”
Section: Demography Of the Neotropical Austral Migrantmentioning
confidence: 99%
“…It is a frugivorous-insectivorous species with an important role as the main disperser of seed of endemic plants of the Patagonian forest (Armesto et al 1987, Amico & Aizen 2005 and as a controller of herbivorous insects of Nothofagus trees (Mazia et al 2009). Th ere are studies of White-crested Elaenia abundance (Brown et al 2007), diet (Grigera 1982, Brown et al 2007, foraging behavior (Chust et al 2012, Cueto et al 2016a, functional role (Mazia et al 2009, Cavallero et al 2013, and migration routes (Marini & Cavalcanti 1990, Capllonch et al 2011, Cueto et al 2016b, Bravo et al 2017, but its survival has never been studied, as well as the relationship between its demographic parameters with environmental factors.…”
Section: Demography Of the Neotropical Austral Migrantmentioning
confidence: 99%
See 1 more Smart Citation